Nontaxation and representation : the fiscal foundations of political stability - Morrison, Kevin M. (Cambridge studies in comparative politics., 2014)
"Does oil make countries autocratic? Can foreign aid make countries democratic? Does taxation lead to representation? In this book, Kevin M. Morrison develops a novel argument about how government revenues of all kinds affect political regimes and their leaders. Contrary to conventional wisdom, Morrison illustrates that taxation leads to instability, not representation. With this insight, he extends his award-winning work on nontax revenues to encompass foreign aid, oil revenue, and intergovernmental grants and shows that they lead to decreased taxation, increased government spending, and increased political stability. Looking at the stability of democracies and dictatorships as well as leadership transitions within those regimes, Morrison incorporates cross-national statistical methods, formal modeling, a quasi-experiment, and case studies of Brazil, Kenya and Mexico to build his case. This book upends many common hypotheses and policy recommendations, providing the most comprehensive treatment of revenue and political stability to date"--